2019
DOI: 10.1007/s13205-019-1728-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of the metal tolerance protein (MTP) family in grape (Vitis vinifera L.)

Abstract: Metal tolerance proteins (MTPs) play an important role in the transport of metals at the cellular, tissue and whole plant levels. In the present study, 11 MTP genes were identified and these clustered in three major sub-families Fe/Zn-MTP, Zn-MTP, and Mn-MTP, and seven groups, which are similar to the grouping of MTP genes in both Arabidopsis and rice. Vitis vinifera metal tolerance proteins (VvMTP) ranged from 366 to 1092 amino acids, were predicted to be located in the cell vacuole, and had four to six putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 85 publications
(90 reference statements)
5
29
1
Order By: Relevance
“…Compared with that of previous report, three new MTP genesn were found in P. trichocarpa [20]. The number of MTPs in P. trichocarpa was only second to N. tabacum among the plant species in which the MTPs have been identified [5,8,[22][23][24][25][26][27][28]. However, despite the large number of PtrMTPs, the homolog of AtMTP2 in P. trichocarpa was not detected.…”
Section: Evolution and Differentiation Of Ptrmtp Genes As Well As Thecontrasting
confidence: 62%
“…Compared with that of previous report, three new MTP genesn were found in P. trichocarpa [20]. The number of MTPs in P. trichocarpa was only second to N. tabacum among the plant species in which the MTPs have been identified [5,8,[22][23][24][25][26][27][28]. However, despite the large number of PtrMTPs, the homolog of AtMTP2 in P. trichocarpa was not detected.…”
Section: Evolution and Differentiation Of Ptrmtp Genes As Well As Thecontrasting
confidence: 62%
“…Similarly, there were at least 20 TaMTP sequences in modern wheat Triticum aestivum (hexaploid, AABBDD) [ 56 ]. However, in sweet orange ( Citrus sinensis ) and grape ( Vitis vinifera ) genomes, there were 12 and 11 members of CitMTPs and VvMTPs, respectively [ 14 , 57 ]. Additionally, there were 13 CsMTPs identified from Mn hyperaccumulator tea plants ( Camellia sinensis ) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is limited experimental evidence that plant MTPs are involved in high salinity and drought tolerance, some previous reports indicated that MTPs might be related to some adaptations to abiotic stressors, except HMs. The expression of Arabidopsis MTP s was determined under various abiotic stressors in both root and shoot tissues by RNA-seq, and AtMTP9 showed the highest level of expression in response to salt and high osmotic stress [ 57 ]. A cation diffusion facilitator gene from soybean, GmCDF1 ( GmMTP12 ), negatively regulates salt tolerance by regulating K + -Na + homeostasis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metal tolerance proteins (MTPs) are crucial for metal transport at the cellular, tissue, and whole plant levels [81]. Fu et al (2017) observed that several CitMTP genes are significantly upregulated under Cu toxicity [82].…”
Section: Cuo-nps Transportmentioning
confidence: 99%